2013
DOI: 10.1089/jop.2012.0144
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Three Different Intravitreal Injection Techniques on Vitreous Reflux and Intraocular Pressure

Abstract: Double-plane tunnel injection prevents VR from the injection site and has no additional complications than other techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In other studies, the subconjunctival reflux occurred in between 17 [18] and 38% [19] of the eyes. The presence of a subconjunctival reflux depended on the intravitreal injection technique (in order of decreasing reflux rate: straight, oblique and double-plane tunnel scleral [20] ) and on the diameter of the needle (30 G causes less reflux than 27 G, particularly when the injection is not beveled [21] ). Since the injected dose and volume of the drug as well as the injection technique and needle diameter were the same in all cases, it is unlikely that these variables were the cause of the IOP elevation.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, the subconjunctival reflux occurred in between 17 [18] and 38% [19] of the eyes. The presence of a subconjunctival reflux depended on the intravitreal injection technique (in order of decreasing reflux rate: straight, oblique and double-plane tunnel scleral [20] ) and on the diameter of the needle (30 G causes less reflux than 27 G, particularly when the injection is not beveled [21] ). Since the injected dose and volume of the drug as well as the injection technique and needle diameter were the same in all cases, it is unlikely that these variables were the cause of the IOP elevation.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that smaller bore needles have less postinjection reflux and a higher IOP. 50,69,87,88 Similarly, tunneled injection techniques allow the needle track to be pinched off by the edge of the sclera, reducing the amount of reflux and increasing post-injection IOP. 69,87 A second important risk factor for severe, acute ocular hypertension and delayed recovery is a prior history of glaucoma.…”
Section: Bmentioning
confidence: 99%
“…50,69,87,88 Similarly, tunneled injection techniques allow the needle track to be pinched off by the edge of the sclera, reducing the amount of reflux and increasing post-injection IOP. 69,87 A second important risk factor for severe, acute ocular hypertension and delayed recovery is a prior history of glaucoma. 10,66 Bakri et al found that 10 minutes after IVI of bevacizumab, triamcinolone, or pegaptanib, only 75% of glaucomatous patients recovered to an IOP of less than 35 mmHg in contrast with 95.5% of patients without glaucoma.…”
Section: Bmentioning
confidence: 99%
“…Tunneled injections through the sclera are associated with less vitreous reflux compared with straight injections that enter the sclera perpendicularly [178180]. The most commonly used needle size for anti-VEGF injections is 30G [48].…”
Section: Reviewmentioning
confidence: 99%
“…The reduced vitreous reflux with 32G needles or tunneled injections is associated with a higher immediate, though transient, intraocular pressure (IOP) elevation [179, 180, 184, 185]. Hoang et al [184] have reported that repeated intravitreal injections in an eye may be complicated by sustained elevations in IOP.…”
Section: Reviewmentioning
confidence: 99%